The Relationship Between Knowledge And Parity Of Pregnant Women And The Activeness Of First Trimester Antenatal Care Visits In The Working Area Of The Ulilin Health Center, Merauke District - Esty Aprilia Sabteka; Erma Retnaningtyas; Miftakhul Muslichah; Hans Angelius Suharto (Journal of Health Science Community, 2024)
Antenatal Care (ANC) examination is a pregnancy examination which aims to improve the physical and mental health of pregnant women optimally, so that they are able to face the period of childbirth, postpartum, preparation for exclusive breastfeeding, and the return to normal reproductive health. This study aims to determine the relationship between knowledge and parity of pregnant women on the activity of first trimester antenatal care visits in the Ulilin Community Health Center Working Area, Merauke Regency in 2023. This research uses a research design Observational Analytics with approach cross sectional. With technique purposive sampling A sample of 24 respondents was obtained, the independent variables were knowledge and parity using a questionnaire and the dependent variable was activeness of first trimester antenatal care visits using observation. Statistical tests are used Chi-Square to find out the relationship between the two variables. The results of research from 24 respondents showed that the majority of respondents had insufficient knowledge criteria, 14 respondents (46.7%), most of the parity mothers were primiparous, 16 respondents (53.3%). And it was found that most of the respondents who had criteria for not regularly making antenatal care visits were 18 respondents (60%). Analysis uses statistical tests Chi-Square results were obtained p = 0.047 < 0.05, then H0 is rejected and H1 is accepted, which means there is a relationship between the level of knowledge and the activeness of antenatal care visits in the Ulilin Community Health Center working area and the result is p = 0.027 < 0.05, then H0 is rejected and H1 is accepted, which means there is a parity relationship with activeness on First trimester antenatal care visit in the Ulilin Community Health Center working area. Providing more education is aimed at the benefits and impacts of irregular Antenatal Care (ANC) visits, thereby creating confidence in pregnant women and providing sufficient information about ANC.